STRATEGI PEMENANGAN DPD PARTAI KEADILAN SEJAHTERA DALAM PEMILU LEGISLATIF KOTA PEKANBARU TAHUN 2019 - Dyaz Fernandez. K; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In this research, in the 2019 legislative election, there was a very signivicant increase in vote acquisition which led to an increase in the acquisition of PKS cadre seats in the Pekanbaru City DPRD. This can be seen from the increase of 31,816 votes in 2019, where in the 2014 election only 21,973 votes were obtained, which researchers tried to formulate with the following questions “what is the winning strategy implemented by the prosperous justice party in the legislative election of Pekanbaru City 2019.” The purpose of this research is in order to know what strategies are  the carried out by the DPD PKS Pekanbaru CityThe research method uses a qualitative approach where this research produces descriptive data. The research was conducted at the DPD PKS Pekanbaru City Office.Based on the research results, it can be concluded that there are 2 strategies used, namely defensive, both of which have an effect on the increase in the vote of the PKS party it self compared to the previous election. PKS winning factors include the hard work of the cadres and the character of the obstacle factors are the uneven distribution of cadres and low level of cadres and the low level of political education among the voters.Keywords : Winning Strategy, Legislative Elections 2019.